Epigenetics changes caused by the fusion of human embryonic stem cell and ovarian cancer cells. Issue 5 (16th September 2016) - He, Ke; Qu, Hu; Xu, Li-Nan; Gao, Jun; Cheng, Fu-Yi; Xiang, Peng; Zhou, Can-Quan
Abstract : To observe the effect of gene expression and tumorigenicity in hybrid cells of human embryonic stem cells (hESCs) and ovarian cancer cells in vitro and in vivo using a mouse model, and to determine its feasibility in reprogramming tumour cells growth and apoptosis, for a potential exploration of the role of hESCs and tumour cells fusion in the management of ovarian cancer. Stable transgenic hESCs (H1) and ovarian cancer cell line OVCAR-3 were established before fusion, and cell fusion system was established to analyse the related indicators. PTEN expression in HO-H1 cells was higher than those in the parental stem cells and lower than those in parental tumour cells; the growth of OV-H1 (RFP+GFP) hybrid cells with double fluorescence expressions were obviously slower than that of human embryonic stem cells and OVCAR-3 ovarian cancer cells. The apoptosis signal of the OV-H1 hybrid cells was significantly higher than that of the hESCs and OVCAR-3 ovarian cancer cells. In vivo results showed that compared with 7 days, 28 days and 35 days after inoculation of OV-H1 hybrid cells; also, apoptotic cell detection indicated that much stronger apoptotic signal was found in OV-H1 hybrid cells inoculated mouse. The hESCs can inhibit the growth of OVCAR-3 cells in vitro by suppressing p53 and PTEN expression to suppress the growth of tumour that may be achieved by inducing apoptosis of OVCAR-3 cells. The change of epigenetics after fusion of ovarian cancer cells and hESCs may become a novel direction for treatment of ovarian cancer.